A case study of FEA-based crash sensing system calibration. (20th February 2004) - Lin, Chin-Hsu; Neal, Mark O.; Wang, J.T.
A case study of using non-linear finite element analyses to aid in calibrating an airbag crash sensing system is presented. Details that are crucial for using a single vehicle model to simulate multiple testing conditions were identified and incorporated in a chosen vehicle model. The vehicle model was then used to simulate a set of no-deployment and all-deployment calibration events. The simulated results were compared with test data to assess the capability of the existing non-linear finite element analysis in aiding sensing system calibration.